Strategic Solution Model Revitalization of the Role of Actor Network in Accelerating Stunting Rate Reduce in “Quality Family (KB)” Villages, Salatiga City - Daru Purnomo; Sri Suwartiningsih; Jodelin Muninggar; Suryo Sakti Hadiwijoyo (Global Writing Academica Researching and Publishing, 2022)
The city of Salatiga has launched